ALIH LARAS DALAM GARAP GÊNDER GENDING KÊNCÊNG LARAS PÉLOG PATHÊT NEM - Lia Tri Lestari; Bambang Sosodoro Rawan Jayantoro (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
This study aimed to review, analyze, and describe working on Gendèran gending Kenceng. The song is one of the Surakarta style gendèr repertoire whose source is the laras Slendro pathet Sanga, and the tuning is converted to the laras Pelog pathet Nem. Two problems in this study, namely (1) How to change the laras of Kenceng gending, which was initially a laras slendro pathêt sanga to a laras pélog pathêt nem. (2) why the gending Kenceng is interesting to be converted into a laras pélog pathêt nem. This type of art research is descriptive qualitative research. The work method starts by designing the work, determining the source and type of data, then collecting data. The data were collected by literature study, observation, and interviews. This problem is studied based on the rules in gendèran, the concept of pathet, the idea of garap, and the concept of mungguh. The study's results showed that in changing the laras of the Kenceng gending dish, there was a change in the arrangement of the balungan grooves. In a Kenceng gending, there is also a balungan arrangement that has the potential to be worked on by applying another céngkok gawan gending to be used to Kenceng gending but still in the rules of Surakarta-style karawitan.